αvβ3 integrin expression increases elasticity in human melanoma cells - Lacaria, Leda; Lange, Janina; Goldmann, Wolfgang; Rico, Felix; Alonso, José Luis (Biochemical and Biophysical Research Communications, 2020)
Living cells interact with the extracellular matrix (ECM) transducing biochemical signals into mechanical cues and vice versa. Thanks to this mechano-transduction process, cells modify their internal organization and upregulate their physiological functions differently. In this complex mechanism integrins play a fundamental role, connecting the extracellular matrix with the cytoskeleton. Cytoskeletal rearrangements, such as the increase of the overall contractility, impact cell mechanical properties, the entire cell stiffness, and cell deformability. How cell mechanics is influenced via different integrins and their interaction with ECM in health and disease is still unclear. Here, we investigated the influence of αvβ3 integrin expression on the mechanics of human melanoma M21 cells using atomic force microscopy and micro-constriction. Evidence is provided that (i) αvβ3 integrin expression in human melanoma cells increases cell stiffness in both adherent and non-adherent conditions; (ii) replacing αvβ3 with αIIbβ3 integrin in melanoma cells, cell stiffness is increased under adherent, while decreased under non-adherent conditions; (iii) αvβ3 integrin cell stiffening is also maintained when cells adhere to fibronectin, but this phenomenon does not strongly depend on the fibronectin concentration. In all, this study sheds light on the role of αvβ3 in regulating cellular mechanics.
CRIS-Team Scopus Importer:2020-03-20
Keywords: and αIIbβ3; Atomic force microscopy; Cell elasticity; Integrin αvβ3; M21 human melanoma cell; Micro-constrictions; α5β1